1996
DOI: 10.1159/000237312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KW-4679, a New Orally Active Antiallergic Drug, on Antigen-Induced Bronchial Hyperresponsiveness, Airway Inflammation and Immediate and Late Asthmatic Responses in Guinea Pigs

Abstract: We investigated the effects of KW-4679, an antiallergic drug, on the development of bronchial hyperresponsiveness, airway inflammation and early and late asthmatic responses following aerosol antigen challenge in guinea pigs actively sensitized by the inhalation of aerosolized ovalbumin. Pretreatment with KW-4679 (10 mg/kg, p.o.) 1 h before antigen challenge prevented the development of bronchial hyperresponsiveness to inhaled methacholine. Examination of the bronchoalveolar lavage fluid 24 h after antigen cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…on the infiltration of eosinophils into the airway (12). Olopatadine at doses of 1 and 10 mg/ kg clearly inhibited the increase in R L at IAR and LAR (12). These results indicate that olopatadine could be useful in the treatment of bronchial asthma.…”
Section: -1 Inhibitory Effects On Experimental Allergic Responses Imentioning
confidence: 69%
See 3 more Smart Citations
“…on the infiltration of eosinophils into the airway (12). Olopatadine at doses of 1 and 10 mg/ kg clearly inhibited the increase in R L at IAR and LAR (12). These results indicate that olopatadine could be useful in the treatment of bronchial asthma.…”
Section: -1 Inhibitory Effects On Experimental Allergic Responses Imentioning
confidence: 69%
“…Examination of the bronchoalveolar lavage fluid 24 h after antigen challenge revealed the inhibitory effect of olopatadine (1, 3 and 10 mg/ kg, p.o.) on the infiltration of eosinophils into the airway (12). Olopatadine at doses of 1 and 10 mg/ kg clearly inhibited the increase in R L at IAR and LAR (12).…”
Section: -1 Inhibitory Effects On Experimental Allergic Responses Imentioning
confidence: 90%
See 2 more Smart Citations
“…inhibited the production and/or release of TXB2 from leukocytes in bronchial alveolar lavage fluid of guinea pigs (Y. Sasaki, unpublished data). On the other hand, we recently demonstrated that KW-4679 inhibits the an tigen-induced development of AHR through the preven tion of eosinophil infiltration into guinea pig airways using a mild-symptoms experimental model that utilizes a single-antigen challenge with metyrapone (15). Conse quently, although the anti-asthmatic mechanism of KW 4679 has not been fully elucidated, it is considered that not only the inhibition of leukocyte infiltration but also the prevention of the action of chemical mediators (e.g., edema formation) such as TXA2, LTB4, PAF, tachykinins and especially histamine could contribute to the inhibi tory effect of KW-4679 on the development of AHR.…”
mentioning
confidence: 99%